2013
DOI: 10.1097/ico.0b013e31829ebb0d
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Corticosteroid Treatment Improves Corneal Transplant Survival in Mice

Abstract: Purpose To examine the effects of presurgical corticosteroid treatment for normal-risk penetrating keratoplasty (NRPK), high-risk penetrating keratoplasty (HRPK), and high-risk penetrating keratoplasty plus lensectomy. Methods We used 3 corneal transplantation models (NRPK, HRPK, and high-risk penetrating keratoplasty plus lensectomy). For each model, we tried to compare the effect of corticosteroid treatment according to different timetables as follows: The first trial began with a corticosteroid injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Thus, our finding favors the notion that early treatment with GCs is important for promotion of allograft survival. 23 Although we did not evaluate the effects of locally applied GCs, it is likely that systemic infusion of GCs is more effective at inducing MDSC expansion in BM, given the level of GCs in BM after systemic versus local administration. Second, our data suggest that monocytic MDSCs might be a potential cellular source for tolerogenic cell therapy in transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, our finding favors the notion that early treatment with GCs is important for promotion of allograft survival. 23 Although we did not evaluate the effects of locally applied GCs, it is likely that systemic infusion of GCs is more effective at inducing MDSC expansion in BM, given the level of GCs in BM after systemic versus local administration. Second, our data suggest that monocytic MDSCs might be a potential cellular source for tolerogenic cell therapy in transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Some have advocated for the use of steroids prior to high‐risk transplantation but this has been variably adopted. A survey of the Bowman's Club (The UK Society of corneal surgeons) found that topical dexamethasone was used in 33%, oral prednisolone by 22% and single dose IV methylprednisolone (IVMP) by 14% …”
Section: Uses Of Locally Administered Steroidsmentioning
confidence: 99%
“…Kim et al 84 proposed a preoperative use of corticosteroids 2 weeks before the transplantations. They revealed that the pretreatment with corticosteroids decreased the host bed neovascularization in both LR and HR corneal transplantation.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%